ASESMEN KEBUTUHAN KONSELI DALAM PERENCANAAN PROGRAM BIMBINGAN DAN KONSELING DI SEKOLAH MENENGAH PERTAMA - Meiga Latifah Putri Permadin; Herdi Herdi (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2021)
Guidance and counseling programs in junior high schools are arranged based on the needs of students/counselees and school needs. Needs assessment is an activity that aims to find out the real conditions of students that will be used as a basis in planning guidance and counseling programs. A good guidance and counseling program at an educational institution is a well-done plan. The research method used is a literature study. Researchers dig up information through the google scholar search page and DOAJ (Directory Open Access Journal) to find traces of past research related to literacy skills. Through this research, it is expected to know the development of research that has been done about the need assessment in the planning of counseling and counseling programs in junior high schools.